ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MAKANAN MENGGUNAKAN LAYANAN PESAN-ANTAR SHOPEE FOOD (STUDI PADA PENGGUNA SHOPEE FOOD DI KOTA SEMARANG) - Ichawanda Ayu Hamida; Amron Amron (Fakultas Ekonomi Universitas Pekalongan, 2022)
The development of e-commerce in Indonesia today is inseparable from the habits of the people who demand practicality and speed. There is a change in consumer behavior from those who usually buy food offline to now switch to buying food online by utilizing services on the marketplace. This has led to an increase in food-delivery transactions. The purpose of this study is to determine the factors that influence consumer behavior on consumer purchasing decisions in buying food using the Shopee Food delivery service. The sample method used by the author is convenience sampling, which is a sampling technique using a free sample according to the author's wishes. The number of samples is 100 respondents. The results of the study show that the overall factors have a significant effect and have a simultaneous contribution. And partially the factors that have a significant influence are personal factors psychological factors, while social and cultural factors have no significant effect on food purchasing decisions using Shopee Food delivery services.